Validity and inter-observer reliability of subjective hand-arm vibration assessments - Coenen, Pieter; Formanoy, M.; Douwes, M.; Bosch, T.; De Kraker, H. (2014)
Exposure to mechanical vibrations at work (e.g., due to handling powered tools) is a potential occupational risk as it may cause upper extremity complaints. However, reliable and valid assessment methods for vibration exposure at work are lacking. Measuring hand-arm vibration objectively is often difficult and expensive, while often used information provided by manufacturers lacks detail. Therefore, a subjective hand-arm vibration assessment method was tested on validity and inter-observer reliability. In an experimental protocol, sixteen tasks handling powered tools were executed by two workers. Hand-arm vibration was assessed subjectively by 16 observers according to the proposed subjective assessment method. As a gold standard reference, hand-arm vibration was measured objectively using a vibration measurement device. Weighted ?'s were calculated to assess validity, intra-class-correlation coefficients (ICCs) were calculated to assess inter-observer reliability. Inter-observer reliability of the subjective assessments depicting the agreement among observers can be expressed by an ICC of 0.708 (0.511-0.873). The validity of the subjective assessments as compared to the gold-standard reference can be expressed by a weighted ? of 0.535 (0.285-0.785). Besides, the percentage of exact agreement of the subjective assessment compared to the objective measurement was relatively low (i.e., 52% of all tasks). This study shows that subjectively assessed hand-arm vibrations are fairly reliable among observers and moderately valid. This assessment method is a first attempt to use subjective risk assessments of hand-arm vibration. Although, this assessment method can benefit from some future improvement, it can be of use in future studies and in field-based ergonomic assessments. © 2014 Elsevier Ltd and The Ergonomics Society.